ANALYSIS OF THE EFFECT OF SERVANT LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH WORK CREATIVE BEHAVIOR AS AN INTERVENING VARIABLE - Danang Kusumo Projo; Edy Raharja (Lafadz Jaya Publisher, 2023)
This study aims to prove the influence of factorsservant leadershipand organizational culture on employee performance with work creative behavior as an intervening variableoneducational staff employee with ASN status at the Indonesian State Maritime Polytechnic office. Determining the number of samples using the census method where the total population was taken as a sample of 48 people as educational staff employees with ASN status. Data were analyzed using a quantitative approach with the SEM-PLS method through the SmartPLS 3.3 application. The results of the research show that the five hypotheses formed as a whole are acceptable. Servant Leadership has a significant effect on Employee Performance with a p-value of 0.000 <0.05. Organizational Culture has a significant effect on Employee Performance with a p-value of 0.003 <0.05. Servant Leadership has a significant effect on Work Creative Behavior with a p-value of 0.006 <0.05. Organizational Culture has a significant effect on Work Creative Behavior with a p-value of 0.000 <0.05. and Work Creative Behavior has a significant effect on Employee Performance with a p-value of 0.002 <0.05.